Impact of COVID‐19 outbreak in reperfusion therapies of acute ischaemic stroke in northwest Spain. (4th September 2020) - Tejada Meza, H.; Lambea Gil, Á.; Sancho Saldaña, A.; Martínez‐Zabaleta, M.; Garmendia Lopetegui, E.; López‐Cancio Martínez, E.; Castañón Apilánez, M.; Herrera Isasi, M.; Marta Enguita, J.; Gómez‐Vicente, B.; Arenillas, J.F.; Arenaza Basterrechea, N.; et al.
Abstract: Background and purpose: Spain has been one of the countries more heavily stricken by SARS‐CoV‐2, which has had huge implications for stroke care. The aim was to analyse the impact of the COVID‐19 epidemic outbreak on reperfusion therapies for acute ischaemic stroke in the northwest of Spain. Methods: This was a Spanish multicentre retrospective observational study based on data from tertiary hospitals of the NORDICTUS network. All patients receiving reperfusion therapy for ischaemic stroke between 30 December 2019 and 3 May 2020 were recorded, and their baseline, clinical and radiological characteristics, extra‐ and intra‐hospital times of action, Code Stroke activation pathway, COVID‐19 status, reperfusion rate, and short‐term outcome before and after the setting of the emergency state were analysed. Results: A total of 796 patients received reperfusion therapies for ischaemic stroke. There was a decrease in the number of patients treated per week (46.5 patients per week vs. 39.0 patients per week, P = 0.043) and a delay in out‐of‐hospital (95.0 vs. 110.0 min, P = 0.001) and door‐to‐needle times (51.0 vs. 55.0, P = 0.038). Patients receiving endovascular therapy obtained less successful reperfusion rates (92.9% vs. 86.6%, P = 0.016). COVID‐19 patients had more in‐hospital mortality. Conclusion: A decrease in the number of patients benefiting from reperfusion therapies was found, with a delay in out‐of‐hospital and door‐to‐needle times and worse reperfusion rates in northwest Spain. COVID‐19 patients had more in‐hospital mortality.